2022
DOI: 10.1101/2022.12.01.22282886
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Are we really targeting and stimulating DLPFC by placing transcranial electrical stimulation (tES) electrodes over F3/F4?

Abstract: Background: Most transcranial electrical stimulation (tES) clinical trials place target electrodes over DLPFC based on the assumption that it would mainly stimulate the underlying brain region. Here, we assessed delivered electric fields (EF) using a symmetric and asymmetric DLPFC stimulation montage to identify additional prefrontal regions that are inadvertently targeted beyond DLPFC. Methods: Head models were generated from the human connectome project database's T1+T2-weighted MRIs of 80 healthy adults. Tw… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…Another explanation, based on electric field simulations, is that other areas of the PFC were targeted following tDCS, such as the medial PFC. It has been shown that positioning large tDCS electrodes (35cm²) bilaterally (F3/F4 or F4/Fp1) may not maximally target the DLPFC per se, but that hat other parts of the PFC may receive stronger electric field strengths (article in preprint: Soleimani et al, 2022). In addition, future research should also explore the potential impact of laterality in tDCS montage (left vs. right) and their electric field simulation patterns on different forms of cognitive performance during the CECT.…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation, based on electric field simulations, is that other areas of the PFC were targeted following tDCS, such as the medial PFC. It has been shown that positioning large tDCS electrodes (35cm²) bilaterally (F3/F4 or F4/Fp1) may not maximally target the DLPFC per se, but that hat other parts of the PFC may receive stronger electric field strengths (article in preprint: Soleimani et al, 2022). In addition, future research should also explore the potential impact of laterality in tDCS montage (left vs. right) and their electric field simulation patterns on different forms of cognitive performance during the CECT.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with the observation that peak E-fields are typically observed between, rather than directly under, the tDCS electrodes. 66 , 67 …”
Section: Discussionmentioning
confidence: 99%
“…For example, current flow modeling has demonstrated that identical tES parameters result in an over 100% difference in the intensity of the E-field generated in the motor cortex (Evans et al, 2020 ). There is also the potential for unintentional stimulation of off-target regions, especially when individualized modeling is not performed (Soleimani et al, 2023 ).…”
Section: Obstacles To Effective Non-invasive Brain Stimulationmentioning
confidence: 99%